Conceptualizing Sustainable Competitive Advantage: Theories, Themes, and Varying Perspectives (Acta Universitatis Danubius. Œconomica, 2024)
This study conceptualizes sustainable competitive advantage (SCA) by examining the key theories, themes, and perspectives that influence competitive positioning and long-term performance. It addresses theoretical fragmentation and provides a more coherent understanding of SCA theoretical foundation. Building on frameworks such as the Resource-Based View, Dynamic Capabilities View, Structural Approach, and Blue Ocean Strategy, the paper integrates diverse theoretical perspectives to address gaps in the literature and refine the conceptualization of SCA. A semi-systematic, integrative literature review was conducted, analyzing both theoretical and empirical insights on SCA. The review explored the integration of these frameworks and their practical implications for contemporary organizations. The findings reveal that SCA is shaped by the interplay of internal resources and external market positioning. Key elements such as VRIN (valuable, rare, inimitable, and non-substitutable) resources, along with dynamic capabilities that foster adaptability, are essential, though consensus on standardized measurement remains elusive. This study underscores the need for a validated, comprehensive operational framework for SCA measurement, suggesting an integrated approach that combines internal and external strategic factors to enhance strategic management practices. This paper presents an interdisciplinary and integrated SCA framework that enhances the understanding of SCA while offering actionable recommendations for organizations aiming to strengthen strategic positioning and performance in a VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) environment.